A new look at the schema therapy model: organization and role of early maladaptive schemas. Issue 4 (4th July 2018) - Bach, Bo; Lockwood, George; Young, Jeffrey E.
Abstract: This study reexamined the organization of Young's 18 early maladaptive schemas and their hypothesized associations with experiences of need-thwarting parental experiences in childhood and the "vulnerable child" mode of emotional distress in adulthood. A large Danish sample ( N  = 1054) of 658 clinical- and 391 nonclinical adults completed measures of early maladaptive schemas, parenting styles, and the vulnerable child mode. We identified four higher-order schema domains as most appropriate in terms of interpretability and empirical indices ("Disconnection & Rejection", "Impaired Autonomy & Performance", "Excessive Responsibility & Standards", and "Impaired Limits"). All four schema domains were differentially associated with conceptually relevant need-thwarting parental experiences. Apart from "Impaired Limits", the schema domains meaningfully accounted for the association between need-thwarting parental experiences in childhood and emotional states of feeling like a "vulnerable child" in adulthood. We conclude that four domains of early maladaptive schemas are empirically and conceptually consistent with Young's schema therapy model of personality pathology and longstanding emotional disorders. Findings warrant replication using different populations and if possible a prospective multi-method design. A scoring key for computing the four schema domains is provided.